PENINGKATAN KEMAMPUAN SMASH OPEN MELALUI ALAT DRILL SMASH - Alamsyah, Alamsyah; Supriatna, Eka; Samodra, Y. Touvan Juni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractMastery of the basic smash techniques in volleyball is important. The success of a team in winning a volleyball match is largely determined by the smash. Therefore, the researcher gave a smashing exercise using the method of the smash drilling tool. This study aims to find out the improvement of the smash drill tool on the ability of smash open in volleyball, hoping to give good results so it can be applied in the training process. The method used in this research is an experiment with pre-experimental design. The population in this study was thirty-four male volleyball athletes at the Pontianak Brojomusti club, and ten athletes were chosen as the sample in this study. The instrument used in this study is a smashing test, in which each athlete smashes open 10 times with different numbers in each corner. Before conducting the hypothesis test, the researcher did the prerequisite tests such as the Lillefors Test, Homogeneity Test and Influence Test with T-Test. Based on the results of the calculation of tcount 19.01> ttable 2.26 it can be concluded that Ha was accepted, it means that the applied training method affects the ability of the smash open. Calculation of the effect size obtained is 21.37%.Key Words : Smash Open, Drilling tool